Selecting for rust (Puccinia psidii) resistance in Eucalyptus grandis in São Paulo State, Brazil - Silva, Paulo Roberto Arbex [UNESP]; Miranda, Aline C. [UNESP]; Moraes, Mario L.T. [UNESP]; Furtado, Edson Luiz [UNESP]; Stape, José Luiz [UNESP]; Alvares, Clayton Alcarde; Sentelhas, Paulo Cesar; Mori, Edson Seizo [UNESP]; Sebbenn, Alexandre M. (Elsevier, 2013)
In Brazil, Eucalyptus grandis is a key species for wood production. However, some genotypes are susceptible to rust (Puccinia psidii), mainly in São Paulo State, where climatic conditions are favorable for its development. Rust represents a high economic risk to forest companies because of the high potential of damage to commercial eucalypt plantations. The aims of the present study were (i) to select progenies of E. grandis for stability and adaptability regarding resistance to rust at different locations; (ii) compare the selections under these different climatic conditions; and (iii) compare rust severity in the field with the theoretical model. We observed that climatic conditions were extremely influential factors for rust development, but even under favorable conditions for disease development, we found rust-resistant progenies. In sites unfavorable for rust development, we detected highly susceptible progenies. We found significant correlation among the genetic material, environmental conditions and disease symptoms, however, we observed a simple genotype-environmental interaction and significant genetic variability among the progenies. The average heritability was high among the progenies in all sites, indicating substantial genetic control for rust resistance. We also observed a good relationship between rust severity in the field and the theoretical model that considered annual average temperature and leaf wetness. © 2013 Elsevier B.V.
Keywords: Agrometeorology; Disease resistance/tolerance; Ecological zoning; Genetic parameters; Stability and adaptability analysis; Tree breeding; Disease resistance; Environmental conditions; Eucalypt plantations; Favorable conditions; Influential factors; Ecology; Forestry; agrometeorology; deciduous tree; disease resistance; disease severity; forest management; genetic variation; genotype-environment interaction; planation; rust disease; symptom; wood; Breeding; Diseases; Trees; Brazil; Sao Paulo [Brazil]